AB0194 Peripheral Blood Perfusion as Evaluated by Laser Speckle Contrast Analysis in Different Areas of Hands in Primary Raynaud's Phenomenon and Healthy Subjects. (9th June 2015) - Sulli, A.; Ruaro, B.; Smith, V.; Pizzorni, C.; Ravera, F.; Cariti, C.; Cutolo, M.
Abstract : Background: Laser speckle contrast analysis (LASCA) is a technique to assess blood perfusion in different body areas (1-2). Objectives: To investigate peripheral blood perfusion (BP) by LASCA in different areas of hands in primary Raynaud's phenomenon (PRP) patients and healthy subjects (CNT), looking for differences between the groups. Methods: 31 PRP patients (LeRoy criteria) (3) (mean age 48±18 years, mean Raynaud duration 6±2 years) and 51 CNT (mean age 51±16 years) were enrolled, after informed consent. BP was bilaterally assessed by LASCA at the level of fingertips, periungual areas, dorsal and palmar surface of proximal phalanges, dorsum and palm of both hands, and the BP was calculated as perfusion units (PU) (1, 2). All subjects stayed in a room at constant temperature (23°C) for 20 minutes before the analysis. PRP subjects discontinued treatment with oral vasodilators, if present, at least seven days before the examination. Statistical analysis was carried out by non parametric tests. Results: PRP patients showed a statistically significant lower BP than CNT at the level of fingertips (median 86 and 181 PU, respectively, p<0.0001), periungual (median 75 and 142 PU, respectively, p<0.0001), palmar aspect of proximal phalanges (median 71 and 129 PU, respectively, p<0.0001), and palm areas (median 61 and 108 PU, respectively, p<0.0001). On the contrary, the two groups displayed similar BP values at the level of the other areas of hands (dorsum and dorsal phalanges). The gradients of BP fingertip-phalanx-palm and periungual-phalanx-dorsum were significantly lower in PRP patients when compared with CNT (p<0.0001). Conclusions: This study demonstrates that blood perfusion is reduced only in selected areas of the hands (where microcirculation is prevalent), sparing dorsal surface of phalanges and dorsum of hands (where macrocirculation is predominant). Therefore, present results are in agreement with the fact that macrocirculation is usually not involved in PRP (4). References: Ruaro B, et al. Ann Rheum Dis 2014;73:1181-5. Sulli A, et al. Ann Rheum Dis 2014;73:2059-61. LeRoy EC, et al. Clin Exp Rheumatol.1992;10:485-8. Cutolo M et al. Nat Rev Rheumatol. 2010;6:578-87. Disclosure of Interest: None declared